The eclipse of a plural musician: The career of António Augusto Urceira - Rodrigues Prada Soares, Teresinha (2023)
The text presents the results of research on the Lisbon musician António Augusto Urceira, in relation to his biographical data and his musical career. As regards his artistic career, interpretation of the data showed plurality to be the best way of describing his activity, which is set out in chronological order – from the end of the Monarchy to the arrival of the Republic, and ending in the Estado Novo. By way of conclusion, we come to recognise that his work with the classical guitar was the best documented and, through an analysis, we perceive how innovative the repertoires that he chose and his performance were for the first half of the 20th century.